Development of a Measurement and Control Method Enabling the Determination of the Gas Phase Content in a Liquid Metal or Alloy - Bydalek, A.W.; Biernat, S. (Archives of Foundry Engineering, 2026)
This article presents various possibilities for testing the degree of gassed of liquid metals. This phenomenon poses a significant problem in the foundry industry, therefore, it is crucial to conduct extraction processes and develop a rapid and accurate method for assessing the gas phase content in the alloy. In addition to analysing methods already known and used in industry and laboratories, the authors present possible research directions using innovative ideas. To confirm hypotheses, they build a test rig and then conduct a series of tests that yield interesting results. The authors studied a lead alloy (Pb-Sn). The alloy was analyzed under the same conditions, subjecting it to moderate and then intense gassed. The results were compared with those of a reference test of a ungassed alloy. It was observed that the ungassed alloy showed a linear increase in the resistance of the liquid metal over the tested temperature range. With the gassed charge, there were either slight changes or the resistance value remained constant over the tested temperature range. The research method not only provides a quick answer but also allows for determining whether the degassing process can be interrupted or should be continued. The method is based on examining the micro-resistance of the system at a given temperature using measuring probes placed in the liquid alloy. By examining a reference sample and determining its reference system parameters, the user can quickly assess the charge in terms of the degree of gassed for each subsequent batch of material prepared in the industrial process.